2018
DOI: 10.1038/s41598-018-32764-w
|View full text |Cite
|
Sign up to set email alerts
|

Authenticity and geographic origin of global honeys determined using carbon isotope ratios and trace elements

Abstract: Honey is the world’s third most adulterated food. The addition of cane sugar or corn syrup and the mislabelling of geographic origin are common fraudulent practices in honey markets. This study examined 100 honey samples from Australia (mainland and Tasmania) along with 18 other countries covering Africa, Asia, Europe, North America and Oceania. Carbon isotopic analyses of honey and protein showed that 27% of commercial honey samples tested were of questionable authenticity. The remaining 69 authentic samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
66
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 43 publications
(85 reference statements)
5
66
1
Order By: Relevance
“…The same conclusion has been previously reached by Krops et al [10] when classifying robinia, lime and chestnut honeys from different Slovenian locations, who finally used linear discriminant analysis (LDA); approach also followed in other works [9,11]. Also Zhou et al [3] concluded that no visual clustering of honeys of different geographical origin was achieved by PCA, even using six principal components, making use in this case of canonical discriminant analysis (CDA) for classification purposes. Support vector machine, multilayer perceptron and random forest were used by Batista et al [12].…”
Section: Principal Component Analysissupporting
confidence: 58%
See 3 more Smart Citations
“…The same conclusion has been previously reached by Krops et al [10] when classifying robinia, lime and chestnut honeys from different Slovenian locations, who finally used linear discriminant analysis (LDA); approach also followed in other works [9,11]. Also Zhou et al [3] concluded that no visual clustering of honeys of different geographical origin was achieved by PCA, even using six principal components, making use in this case of canonical discriminant analysis (CDA) for classification purposes. Support vector machine, multilayer perceptron and random forest were used by Batista et al [12].…”
Section: Principal Component Analysissupporting
confidence: 58%
“…Around 20% of the analysed samples (blends of EU honeys, or originating from one specific Member State (MS)), very likely contained added sugars, such as corn syrups derived from starch and inverted sucrose syrup [2]. The outcome of a recent study carried out with Australian honeys [3] showed that about 27% of the commercially available honey samples analysed were of "questionable authenticity. "…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is therefore difficult to use this technique for routine surveillance (Rossier et al, 2014). IRMS has been widely successfully used for geographic delineation of several processed high-value processed food products such as honey (Zhou et al, 2018), fruit juice (Dasenaki and Thomaidis, 2019), and wine (Christoph et al, 2015); and although IRMS is effective for a broad range of products, for raw unprocessed food products -particularly those being harvested from the environment, geographic origin may be more easily elucidated by using the composition of the microbiome as a marker.…”
Section: Introductionmentioning
confidence: 99%